Fatigue, Depression, and Anxiety Among Ambulating Multiple Sclerosis Patients - AlSaeed, Safanah; Aljouee, Tamadher; Alkhawajah, Nuha M.; Alarieh, Rola; AlGarni, Hanan; Aljarallah, Salman; Ayyash, Mohsen; Abu-Shaheen, Amani (Frontiers in Immunology, 2022)
Background Multiple sclerosis (MS) is an inflammatory disease associated with adverse effects: including depression, anxiety, fatigue, which may affect physical activity and the quality of life (QoL) among patients with MS (pwMS). Objective This study aims to assess the prevalence of depression, anxiety, and fatigue among pwMS who have no physical disability in Saudi Arabia, and demonstrate any correlation between these factors and physical activity as well as the QoL. Methods A cross-sectional study was conducted in the Neuroimmunology outpatient clinics in King Fahad Medical City (KFMC) and King Saud University Medical City (KSUMC) in Riyadh City, KSA. The Arabic version of the Hospital Anxiety and Depression Scale (HADS) was used to measure anxiety and depression levels. The HADS scores were then categorized into three levels according to the total points: normal (0–7 points), borderline (7–10 points), and anxiety/depression (11 – 21 points). The Arabic version of the Fatigue Severity Scale (FSS) was used to measure fatigue (cut-off point ≥5). The physical activity was measured by the Arabic version of the short form of the International Physical Activity Questionnaire (IPAQ), which measure time spent walking, moderate- and vigorous-intensity physical activity of at least 10 minutes duration. The QoL was also measured by the Arabic version of the EuroQOL five-dimensional (EQ-5D-3L) instrument (i.e., mobility, self-care, usual activities, pain/discomfort, and anxiety/depression). Results A total of 323 pwMS participated in this study, 83 had scores that indicated anxiety (25.7%) and 44 had depression (13.6%). The majority of patients had scores with the normal range of depression and anxiety (70% and 57% respectively). The mean of EuroQol Group visual analogue scale (EQ-VAS) score was 80.43 (SD=19.8). 156 (48.3%) out of 323 pwMS reported fatigue while the remainder had no fatigue (n=167, 51.7%). The results indicate that only 143 patients (44.3%) had participated in vigorous physical activity during the last 70 days, with a median of 3 days per week (IQR= 5–3) and a median of 60 minutes per day 0 (Interquartile range: IQR = 60–30). Only 149 patients (49.2%) had patricpated in moderate physical activities during the previous week with a median of 3 days per week (IQR = 5–3) and a median of 40 minutes per day (IQR = 60–30). 194 patients had participated in walking activities (60.0%) with a median of 5 days per week (IQR = 7–3) and a median of 45 minutes per day (IQR = 60–30). The results revealed that fatigue was positively correlated with depression (r = 0.407, p-value < 0.001) and anxiety (r = 0.289, p-value < 0.001). Conclusion The current study shows depression, anxiety, and fatigue tend to be correlated and clustered together among pwMS in our cohort. However, fatigue is not associated with the intensity of physical activity undertaken. The results of this study are important for the improvement of the clinical management of MS patients.